Wartość genetyczno-hodowlana wybranych pochodzeń jodły olbrzymiej (Abies grandis Lindl.) w warunkach Beskidu Sądeckiego - Kulej, Marian (Leśne Prace Badawcze, 2010)
This research investigated seven provenances of grand fir ( Abies grandis Lindl.), from Regions I and II of its natural range of distribution, growing in the experimental area of the Forest Experimental Station in Krynica (LZD Krynica) at 700–720 m above sea level. The survival of individual grand fir provenances between the years 1983–2006 was subject to a detailed analysis. The influence of provenance (genotype) and location (environment) on survival was tested by two-factor ANOVA and Snedecor’s (F) test. The genetic component was determined as the percent of provenance variation within the total genetic variation. The dependence of survival of the provenances on the location of their mother stands was determined using Spearman’s rank correlation coefficient. The silvicultural value of tested provenances was assessed using the Finlay-Wilkinson method. The survival of grand fir in the experiment was principally dependent on its origin. This is confirmed by the share of the variation attributable to genotype (60%) in the total genetic variation (40%). Inter-provenance variation in the percentage of tree survival from each provenance followed a clinal trend, as it was dependent on both the elevation above sea level and the latitude of origin of the mother stands. By combining survival and height data, the projected growth of grand fir provenances could be estimated, with a high likelihood, from the height of trees aged 8–14 years. Analysis of the genotype-(provenance)-×-observation-year (age) interaction effect (G × Eage) allowed the stability of current growth rates to be determined, but only for provenances with extremely tall trees. In these provenances (Bear Mountain, Buck Creek, Crescend Creek, Santiam Summit), effective selection is possible when they are at the juvenile phase of growth. So far our research suggests that from a silvicultural point of view the provenance of the grand fir from Salmon River on Vancouver Island in Canada appears to be performing best.